Waqf-linked Unit Trust Funds: A Qualitative Analysis Of Recent Application In Malaysia - Syahnaz Sulaiman; Muhammad Taqi'uddin Mohd Hamzah; Aznan Hasan (USIM Press, 2024)
Vol. 34 No. 3 (2022): ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences